Adoption of E-Learning among Employees in Nepalese Commercial Banks of the Kathmandu Valley - Bishwokarma, Rajak; Chaulagain, Sujan; Acharya, Sita (Journal of Business and Social Sciences Research, 2025)
E-learning systems have emerged as essential tools for boosting the productivity of banking professionals in Nepal. Nonetheless, there is a notable deficiency in research investigating the adoption of e-learning within commercial banks in the country. The study aimed to examine e-learning adoption in Kathmandu Valley’s banking institutions. Utilising a cross-sectional survey with purposive sampling, the researchers collected data from 250 bank employees. Partial Least Squares Structural Equation Modelling (PLS-SEM) were using to test their hypotheses. This study found that Management Support (MS) significantly enhances both the perceived usefulness (PU) and perceived ease of use (PEU) of an e-learning system. Prior Experience (PE) and Computer Proficiency (CP) also showed strong positive effects on these perceptions. Computer Anxiety (CA), however, showed no significant influence on the perceptions of users. In all, the findings underscore the importance of organisational support, user experience, and technical skills in successful e-learning adoption. The study is expected to provide both banking managers and policymakers and represent one or the earliest investigations into e-learning adoption within Nepal’s banking sector, specifically in the Kathmandu valley.